Tonsil histopathology in HIV-infected versus HIV-uninfected adults - Ridwaan Essa; Shivesh Maharaj; Kapila Hari; Shahpar Motakef (AOSIS, 2019)
Background: The relationship between HIV and tonsil malignancy has not been fully investigated and established. Both of these diseases prominently feature in the Otorhinolaryngology clinics. Objective: There is minimal data available on the histopathology of tonsillectomy specimens in the HIV-infected population. This retrospective review compared tonsil histopathology between HIV-infected and HIV-uninfected patients. Methods: Of the 319 adult patients undergoing tonsillectomy (01 July 2005 to 30 June 2015), HIV results were available for 160. The histological findings were compared in the HIV-infected and HIV-uninfected subgroups. The effects of age, HIV status and CD4 count on the risk of malignancy were determined. Results: There were 86 patients who were HIV-infected and 74 were uninfected. Reactive lymphoid hyperplasia was the most common diagnosis in both groups (77%). Malignancies were diagnosed in eight HIV-infected and six HIV-uninfected patients, an insignificant difference. Conclusion: The majority of patients undergoing tonsillectomy had benign conditions. HIV status does not appear to be a specific risk factor for tonsil malignancies, but advanced age may be.